Face identity matching is influenced by emotions conveyed by face and body - Van Den Stock, Jan; de Gelder, Beatrice (Frontiers in Human Neuroscience, 2014)
Faces provide information about multiple characteristics like personal identity and emotion. Classical models of face perception postulate separate sub-systems for identity and expression recognition but recent studies have documented emotional contextual influences on recognition of faces. The present study reports three experiments where participants were presented realistic face-body compounds in a 2 category (face and body) x 2 emotion (neutral and fearful) factorial design. The task always consisted of two-alternative forced choice facial identity matching. The results show that during simultaneous face identity matching, the task irrelevant bodily expressions influence processing of facial identity, under conditions of unlimited viewing (Experiment 1) as well as during brief (750ms) presentation (Experiment 2). In addition, delayed (5000ms) face identity matching of rapidly (150ms) presented face-body compounds, was equally influenced by the body expression (Experiment 3). The results indicate that face identity perception mechanisms interact with processing of bodily and facial expressions.